Multifaceted perspectives about digital home assistants and privacy from older adults with mobility disabilities - Emma Lachs; Tracy L. Mitzner; Husna Hussaini; Wendy A. Rogers (Gerontechnology, 2025)
Background: Digital home assistants (DHAs) can provide support for a wide range of everyday activities. They may be particularly useful for people who are aging, especially those with mobility disabilities, as they are voice-activated. However, barriers such as concerns about privacy could prevent older users from taking advantage of the full po- tential of DHAs. Research Aim: Understanding the attitudes of those aging with mobility disabilities re- garding privacy and DHAs. Methods: Participants were 14 community-dwelling older adults who self-identified as having a long-term mobility disability (i.e., 10 years or more). This mixed-method study included questionnaires and a semi-structured interview administered after 10 weeks of using a DHA. Results: Participants reported using their DHAs for a range of activities, including sup- porting leisure, hobby, entertainment, and health monitoring and maintenance activities. Most had at least some knowledge about how their device worked and how it stored and used their data. Most participants held the belief that control over their personal informa- tion was important and that privacy was highly valued. They expressed nuanced attitudes about privacy issues related to their DHAs. Privacy themes included the idea that their data was not of interest or value; there are no conspiracies directed toward data; there is a need to build confidence or trust with a device and an acknowledgement and acceptance of some risk. A common theme among participants was their appreciation for the benefits of using DHAs despite concerns about privacy risks. Conclusions: Older adults with long-term mobility disabilities reported using their DHAs for a wide variety of activities and perceived benefits from doing so. They reported a range of attitudes about privacy, from a lack of concern to some strong concerns. The findings suggest that increased education and training about privacy risks and protective strategies could facilitate use, given the high value participants placed on privacy.